Assessment of Double Outlet Right Ventricle in Echocardiography - Alshalawi, Fahad; Al Subaie, Mohammed; Alwabel, Sarah (Journal of Neonatal Surgery, 2025)
Background: Double outlet right ventricle (DORV) is a complex congenital heart disease in which both great arteries arise predominantly from the right ventricle, leading to highly variable anatomical and physiological manifestations. Its accurate diagnosis and classification are critical for surgical planning and long-term outcomes. Methodology: This review synthesizes historical definitions, anatomical subtypes, pathophysiological implications, and the pivotal role of echocardiography in assessing DORV. Techniques including 2D echocardiography, Doppler, 3D imaging, and transesophageal echocardiography were evaluated alongside their integration with complementary imaging modalities such as MRI and CT. Clinical applications are illustrated through case studies, emphasizing echocardiography’s diagnostic and perioperative role. Results: Echocardiography remains the gold-standard diagnostic tool, enabling real-time visualization of ventriculoarterial connections, septal defects, outflow tract anatomy, and associated anomalies. It guides surgical planning by defining VSD position, routability, and ventricular function. Case studies highlight echocardiography’s accuracy in detecting anomalies and its correlation with catheterization and MRI. Emerging technologies, including AI-assisted analysis, 3D printing, and hybrid imaging, are enhancing diagnostic precision and personalized surgical strategies. However, challenges such as technical limitations in neonates, operator dependency, and variable expertise persist. Conclusion: Echocardiography is indispensable for the diagnosis, management, and follow-up of DORV, providing essential insights into anatomy, physiology, and surgical planning. Future directions include AI-driven automation, 3D printing for surgical rehearsal, and hybrid imaging for comprehensive cardiac evaluation, all of which will advance precision medicine in congenital cardiology.